Biological Augmented Reality Media for Improving Deaf Students’ Understanding of the Human Immune System - Guchy Falya Maharani; Imas Diana Aprilia (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to measure the effectiveness of the Biological Augmented Reality (BAR) learning media in improving understanding of the